The hypotensive effect of the ruthenium complex [Ru(terpy)(bdq)NO](3+) is higher in male than in female spontaneously hypertensive rats (SHR) - Potje, Simone R. [UNESP]; Hildebrand, Mariana C. [UNESP]; Munhoz, Felipe C. [UNESP]; Troiano, Jessica A. [UNESP]; Pereira, Ariana A. F. [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP]; Silva, Roberto S. da; Bendhack, Lusiane M.; Silva, Cristina Antoniali [UNESP] (Springer, 2014)
We have previously demonstrated that the hypotensive effect of the ruthenium complex [Ru(terpy)(bdq)NO](3+) (TERPY) is slow, long lasting, and does not lead to reflex tachycardia. TERPY's hypotensive effect is increased in hypertensive rats (SHR or 2 kidney-1clip) compared with normotensive rats. We hypothesized that sexual differences could interfere in the hypotensive effects of nitric oxide (NO) donors in SHR. Therefore, here we aimed to investigate the role of sexual differences and endogenous NO in the hypotension induced by TERPY. In conscious, unrestrained animals, we evaluated the hypotensive effect of TERPY before and after the administration of N-nitro-L-arginine methyl ester (L-NAME) (nonselective NO synthase inhibitor), APOCYNIN (NADPH/NOX inhibitor), and TEMPOL (superoxide dismutase mimetic). The hypotensive effect of TERPY was higher in male than in female SHR, but this difference was not observed in the normotensive Wistar group. The effect of TERPY increased after administration of L-NAME in Wistar rats; however, this effect was not altered by L-NAME in SHR. In SHR, sexual dimorphism in TERPY effect was still observed in animals treated with L-NAME. TEMPOL increases the effect of TERPY only in female SHR. After TEMPOL, the sexual dimorphism in TERPY effect was abolished in the SHR group. APOCYNIN increased the effect of TERPY in male and female Wistar and SHR, but maintained the previously observed difference between male and female SHR. Thus, this study shows that TERPY's hypotensive effect increased in male compared with female SHR and indicates that sexual dimorphism in TERPY effect is associated with oxidative stress.
Keywords: SHR; Blood pressure; Gender; Nitric oxide donor; Hypotensive effect; Oxidative stress